A heavy oil chemical composite viscosity reducer and its preparation method and oil production process
By combining aromatic polyisobutylene succinate imine polymer and other materials, the heavy oil chemical composite viscosity reducing agent is prepared, and graft modification and nanoparticle surface modification are carried out, which solves the problem of difficulty in collecting heavy oil in high-temperature and high-salt environments. , and the effect of efficiently reducing the viscosity of heavy oil and improving the yield rate is achieved.
Patent Information
- Application Number
- CN202411587523.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-08
AI Technical Summary
In high-temperature and high-salt environments, single alkali flooding and single polymer flooding are not suitable for unconventional oil reservoirs, and the surfactant stability is poor, making it difficult to meet the needs of third-time oil production technology in oil fields such as Harde Oilfield.
By combining aromatic polyisobutylene succinate imine polymer, amphiphilic active agent, catalyst and organic base, a heavy oil chemical composite viscosity reducing agent is formed. The benzyl group is grafted on the polymer chain to regulate its hydrophilicity and improve salt and temperature resistance by surface modified nanoparticles.
Under high temperature and high salt conditions, heavy oil chemical composite viscosity reducing agent can effectively reduce the viscosity of heavy oil, increase the degree of heavy oil reservoir production, and improve the crude oil extraction rate.
Smart Images

Figure CN119081667B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil and gas field development engineering, and in particular to a heavy oil chemical composite viscosity reducer and a preparation method and an oil production process thereof. Background Art
[0002] With the deepening of oil field development, improving crude oil recovery is facing greater difficulties and challenges. Studies in recent years have shown that single alkali drive and single polymer drive are not suitable for unconventional oil reservoirs, while surfactant drive has greater application potential. However, in high temperature and high salt environments, the stability of surfactants deteriorates and it is difficult to adapt to harsh reservoir conditions. For example, the reservoir temperature of the Hader Oilfield is 110-140℃, the mineralization is 190-230g / L, and the calcium and magnesium ion content exceeds 3000 mg / L. Molecular surfactants are difficult to meet the needs of the tertiary oil recovery technology of the oilfield. Summary of the invention
[0003] In order to solve the above problems, the present invention provides a heavy oil chemical composite viscosity reducer, in which aromatic polyisobutylene succinic acid imide polymer, amphiphilic active agent, catalyst and organic base are compounded, and the aromatic part in the aromatic polyisobutylene succinic acid imide polymer can disperse and inhibit asphaltene aggregation through π-π stacking, hydrogen bond formation, and acid-base interaction. However, the stability of aromatic polyisobutylene succinic acid imide polymer is poor. Adding amphiphilic active agent can not only overcome the problem of poor polymer stability, but also avoid the problem of large amount of energy required when homogeneous modified particles are adsorbed to the interface, thereby having excellent interface performance. Adding catalyst can break C-S, C-N, C-O and other bonds of heavy components in heavy oil to a certain extent, crack the heavy components and permanently reduce viscosity. The heavy oil chemical composite viscosity reducer of the present invention can reduce the viscosity of heavy oil under high temperature and high salt conditions and improve the recovery degree of heavy oil reservoirs.
[0004] The first aspect of the present invention provides a heavy oil chemical composite viscosity reducer, which comprises, by weight, 30-50 parts of an aromatic polyisobutylene succinic imide polymer, 10-20 parts of an amphiphilic active agent, 5-15 parts of a catalyst and 20-30 parts of an organic base.
[0005] Optionally, 35-45 parts of aromatic polyisobutylene succinic acid imide polymer, 15-18 parts of amphiphilic active agent, 8-12 parts of catalyst and 23-27 parts of organic base.
[0006] Alternatively, the synthetic route of aromatic polyisobutylene succinic acid imide polymer is as follows Figure 1 As shown, Figure 1 In, R 1 for , n is 1, R 2is H or OH.
[0007] Optionally, the amphiphilic active agent is one or more of alkyl (benzene) sulfonates, olefin sulfonates, alkylphenol ether sulfonates, polyoxyethylene sorbitan esters and fatty alcohol amine salts.
[0008] Optionally, the aromatic polyisobutylene succinic acid imide polymer is subjected to a modification treatment, wherein the modification treatment process comprises the following steps:
[0009] The aromatic polyisobutylene succinic acid imide and benzyl bromide are mixed, N, N-dimethylformamide is added to dissolve, and then sodium carbonate catalyst is added to reflux reaction at 60° C.-90° C., and then centrifuged and dried in sequence to obtain a benzyl-branched aromatic polyisobutylene succinic acid imide polymer;
[0010] The molecular weight of the aromatic polyisobutylene succinic acid imide is greater than 500, and the molar number of the grafted benzyl groups is 5 to 10. Specifically, the molar number of the grafted benzyl groups refers to the number of grafted benzyl groups in one molecule of the benzyl-grafted aromatic polyisobutylene succinic acid imide polymer.
[0011] Furthermore, the aromatic polyisobutylene succinic acid imide has an amine hydrophilic group, and the amine group can be grafted with a lipophilic benzyl group through an organic reaction. The present invention modifies the aromatic polyisobutylene succinic acid imide polymer, grafts a benzyl group on its chain, and adjusts the hydrophilicity and lipophilicity of the polymer by changing the grafting amount of the benzyl group. The polymer is compounded with other fillers so that the viscosity reducer can quickly emulsify the heavy oil to form a stable O / W type heavy oil emulsion, thereby achieving the purpose of viscosity reduction.
[0012] Optionally, the amphiphilic active agent is an amphiphilic nanoparticle.
[0013] Optionally, the method for preparing the amphiphilic nanoparticles comprises the following steps:
[0014] Taking γ-aminopropyltriethoxysilane solution as a reference, 0.2wt%-0.5wt% nanoparticles are added into 5%-15% γ-aminopropyltriethoxysilane solution by mass, and modified nanoparticles are prepared at 70-80°C; wherein the nanoparticles are one or more of silicon dioxide, aluminum oxide and titanium dioxide.
[0015] The modified nanoparticles are dispersed in liquid paraffin, and then distilled water is added for emulsification, followed by cooling, washing, and drying to obtain solidified paraffin emulsion droplets, wherein the mass ratio of the modified nanoparticles to the liquid paraffin is 1:6-10. Optionally, the mass ratio of the modified nanoparticles to the liquid paraffin is 1:8-10.
[0016] The solidified paraffin emulsion droplets are dispersed in an ethanol solution with a mass fraction of ammonium perfluorooctanoate of 1% to 2%, and then filtered, washed, and the paraffin is dissolved in chloroform, and amphiphilic nanoparticles are obtained by centrifugation.
[0017] Furthermore, the nanoparticles are surface modified with γ-aminopropyltriethoxysilane and perfluorooctanoic acid to obtain amphiphilic nanoparticles having both hydrophilic amino groups and hydrophobic fluorocarbon chains. The amphiphilic nanoparticles have good salt and temperature resistance, and the concentrations of sodium ions, calcium ions, magnesium ions and temperature have little effect on the interfacial activity of the amphiphilic nanoparticles.
[0018] Optionally, the catalyst is an amphiphilic catalyst, wherein NiMo and CoMo are compounded in a mass ratio of 1:1-2. Preferably, the amphiphilic catalyst is compounded in a mass ratio of 1:1.
[0019] Optionally, the organic base is one or more of ethylenediamine, monoethanolamine, diethanolamine, triethanolamine, and diethylenetriamine.
[0020] The second aspect of the present invention provides a method for preparing a heavy oil chemical composite viscosity reducer, the preparation method comprising the following steps:
[0021] Aromatic polyisobutylene succinic acid imide polymer, amphiphilic active agent, catalyst, organic base and water are sequentially added into a reaction container and mixed at a temperature of 60-80° C. to obtain a heavy oil chemical composite viscosity reducer.
[0022] The third aspect of the present invention provides an oil production process, in which the above-mentioned heavy oil chemical composite viscosity reducer is used, wherein the heavy oil is an oil reservoir with a burial depth of more than 1800 meters, a permeability of less than 300mD, a crude oil viscosity of more than 10000mPa·s, a calcium ion content of more than 3000mg / L, and a magnesium ion content of more than 3000mg / L in the heavy oil.
[0023] Compared with the prior art, the present invention achieves at least one of the following beneficial effects:
[0024] (1) The heavy oil chemical composite viscosity reducer of the present invention is compounded with an aromatic polyisobutylene succinic acid imide polymer, an amphiphilic active agent, a catalyst and an organic base, which can reduce the viscosity of heavy oil under high temperature and high salt conditions and improve the recovery rate of heavy oil reservoirs.
[0025] (2) In the heavy oil chemical composite viscosity reducer of the present invention, the aromatic polyisobutylene succinic acid imide polymer is modified and benzyl groups are grafted on its chain. By changing the grafting amount of benzyl groups, the hydrophilicity and lipophilicity of the polymer are regulated. The viscosity reducer is compounded with other fillers so that the heavy oil can be quickly emulsified to form a stable O / W type heavy oil emulsion, thereby achieving the purpose of viscosity reduction.
[0026] (3) In the heavy oil chemical composite viscosity reducer of the present invention, γ-aminopropyltriethoxysilane and perfluorooctanoic acid are used to modify the surface of nanoparticles to obtain amphiphilic nanoparticles having both hydrophilic amino groups and hydrophobic fluorocarbon chains. The amphiphilic nanoparticles have good salt resistance and temperature resistance, and the concentrations of sodium ions, calcium ions, magnesium ions and temperature have little effect on the interfacial activity of the amphiphilic nanoparticles. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0028] Figure 1 The synthetic route of the aromatic polyisobutylene succinic acid imide polymer of the present invention is shown. DETAILED DESCRIPTION
[0029] In order to more clearly illustrate the overall concept of the present invention, a detailed description is given below in an exemplary manner in conjunction with the accompanying drawings.
[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention can also be implemented in other ways different from those described herein, and therefore, the scope of protection of the present invention is not limited by the specific embodiments disclosed below. In the description of this specification, the description of reference terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily have to be directed to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0031] Example 1
[0032] The heavy oil chemical composite viscosity reducer comprises 30 parts of aromatic polyisobutylene succinic acid imide polymer, 10 parts of amphiphilic active agent, 5 parts of catalyst and 20 parts of organic base. The molecular weight of the aromatic polyisobutylene succinic acid imide polymer is greater than 500.
[0033] The amphiphilic active agent is prepared by mixing sodium dodecylbenzene sulfonate and polyoxyethylene sorbitan monostearate in a mass ratio of 1:1. The catalyst is nickel; and the organic base is prepared by mixing ethylenediamine and monoethanolamine in a mass ratio of 1:1.
[0034] Example 2
[0035] The heavy oil chemical composite viscosity reducer comprises 50 parts of aromatic polyisobutylene succinic acid imide polymer, 20 parts of amphiphilic active agent, 15 parts of catalyst and 30 parts of organic base.
[0036] The amphiphilic active agent is obtained by mixing alkylphenol ether sulfonate and polyoxyethylene sorbitan monostearate in a mass ratio of 1:1. The catalyst is nickel; and the organic base is obtained by mixing diethanolamine and triethanolamine in a mass ratio of 1:1.
[0037] Example 3
[0038] The heavy oil chemical composite viscosity reducer comprises 40 parts of aromatic polyisobutylene succinic acid imide polymer, 16 parts of amphiphilic active agent, 10 parts of catalyst and 25 parts of organic base. The molecular weight of the aromatic polyisobutylene succinic acid imide polymer is greater than 800.
[0039] The amphiphilic active agent is prepared by mixing fatty alcohol ammonium salt and polyoxyethylene sorbitol ester in a mass ratio of 1:1. The catalyst is nickel; and the organic base is prepared by mixing ethylenediamine and monoethanolamine in a mass ratio of 1:1.
[0040] Example 4
[0041] Based on Example 3, the main difference is that the aromatic polyisobutylene succinic acid imide polymer is modified, and the modification process includes the following steps:
[0042] The aromatic polyisobutylene succinic acid imide and benzyl bromide are mixed, N, N-dimethylformamide is added to dissolve, and then sodium carbonate catalyst is added to reflux reaction at 60° C., and then centrifuged and dried in sequence to obtain a benzyl-branched aromatic polyisobutylene succinic acid imide polymer;
[0043] The molecular weight of the aromatic polyisobutylene succinic acid imide is greater than 1000, and the molar number of the grafted benzyl group is 5.
[0044] Example 5
[0045] Based on Example 4, the main difference is that the molar number of the grafted benzyl group is 10.
[0046] Example 6
[0047] Based on Example 4, the main difference is that the amphiphilic active agent is amphiphilic aluminum oxide nanoparticles. The preparation method of amphiphilic aluminum oxide nanoparticles comprises the following steps:
[0048] 0.2% aluminum oxide nanoparticles were added into 5% γ-aminopropyltriethoxysilane solution at 70°C to prepare modified aluminum oxide nanoparticles.
[0049] The modified aluminum oxide nanoparticles are dispersed in liquid paraffin, and then distilled water is added for emulsification, followed by cooling, washing and drying in sequence to obtain solidified paraffin emulsion droplets; wherein the mass ratio of the modified aluminum oxide nanoparticles to the liquid paraffin is 1:6.
[0050] The solidified paraffin emulsion droplets were dispersed in an ethanol solution with a mass fraction of 2% ammonium perfluorooctanoate, and then filtered, washed, and the paraffin was dissolved in chloroform, and amphiphilic aluminum oxide nanoparticles were obtained by centrifugation.
[0051] The catalyst is an amphiphilic catalyst, and the amphiphilic catalyst is obtained by compounding NiMo and CoMo in a mass ratio of 1:2.
[0052] Example 7
[0053] Based on Example 4, the main difference is that the amphiphilic active agent is amphiphilic titanium dioxide nanoparticles. The preparation method of amphiphilic titanium dioxide nanoparticles comprises the following steps:
[0054] 0.4% titanium dioxide nanoparticles were added into 10% γ-aminopropyltriethoxysilane solution at 80°C to prepare modified titanium dioxide nanoparticles.
[0055] The modified titanium dioxide nanoparticles are dispersed in liquid paraffin, and then distilled water is added for emulsification, followed by cooling, washing and drying in sequence to obtain solidified paraffin emulsion droplets; wherein the mass ratio of the modified titanium dioxide nanoparticles to the liquid paraffin is 1:8.
[0056] The solidified paraffin emulsion droplets were dispersed in an ethanol solution with a mass fraction of 2% ammonium perfluorooctanoate, and then filtered, washed, and the paraffin was dissolved in chloroform, and the amphiphilic titanium dioxide nanoparticles were collected by centrifugation.
[0057] The catalyst is an amphiphilic catalyst, and the amphiphilic catalyst is obtained by compounding NiMo and CoMo in a mass ratio of 1:1.
[0058] Comparative Example 1
[0059] The main difference is that the aromatic polyisobutylene succinic acid imide polymer is not contained.
[0060] Comparative Example 2
[0061] The main difference is that the amphiphilic active agent is not contained on the basis of Example 1.
[0062] Comparative Example 3
[0063] The main difference is that the method is based on Example 1 and does not contain a catalyst.
[0064] Performance Testing
[0065] 1. According to the Petroleum and Natural Gas Industry Standard SY / T5270-1999 of the People's Republic of China, the interfacial tension between oil and water of the viscosity reducers of Examples 1-7 and Comparative Examples 1-3 of the present application was tested, and the addition amount of the heavy oil chemical composite viscosity reducer was 1%. The test results are shown in Table 1 below.
[0066] Oil samples in the experimental group: the experimental temperature was 200°C, the viscosity of the heavy oil was 12000 mPa·s, the calcium ion content in the heavy oil was 3500 mg / L, and the magnesium ion content was greater than 3500 mg / L.
[0067] Water samples in the experimental group: mineralization 50000-80000 TDS, calcium ion content greater than 3000 mg / L, magnesium ion content greater than 3000 mg / L.
[0068] Viscosity reduction rate determination: Test at 200°C according to method 6.4 in Q / SH10202193-2018.
[0069] Table 1
[0070]
[0071] With reference to Table 1, it can be seen that the heavy oil chemical composite viscosity reducer of the present invention can reduce the tension between the oil and water interface to nearly zero, and the viscosity reduction rate is not less than 97%.
[0072] According to SY / T5358-2010 "Reservoir Sensitivity Flow Experiment Evaluation Method", the crude oil recovery rate can be increased to more than 98% by the heavy oil chemical composite viscosity reducer of the present application. The heavy oil chemical composite viscosity reducer of the present invention can reduce the viscosity of heavy oil under high temperature and high salt conditions and improve the recovery of heavy oil reservoirs.
[0073] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A heavy oil chemical composite viscosity reducer, characterized in that: The heavy oil chemical composite viscosity reducer comprises, by weight, 30-50 parts of aromatic polyisobutylene succinic acid imide polymer, 10-20 parts of amphiphilic active agent, 5-15 parts of catalyst and 20-30 parts of organic base; The structure of aromatic polyisobutylene succinimidyl polymer is shown below: , R 1 for , n is 1, R 2 is H or OH; The amphiphilic active agent is one or more of alkylbenzene sulfonate, olefin sulfonate, alkylphenol ether sulfonate, polyoxyethylene sorbitan ester and fatty alcohol amine salt, or the amphiphilic active agent is amphiphilic nanoparticles; The method for preparing amphiphilic nanoparticles comprises the following steps: Adding 0.2%-0.5% nanoparticles into 5%-15% γ-aminopropyltriethoxysilane solution at 70-80° C. to obtain modified nanoparticles; wherein the nanoparticles are one or more of silicon dioxide, aluminum oxide, and titanium dioxide; Dispersing the modified nanoparticles into liquid paraffin, then adding distilled water for emulsification, and then sequentially cooling, washing, and drying to obtain solidified paraffin emulsion droplets; wherein the mass ratio of the modified nanoparticles to the liquid paraffin is 1:(6-10); The solidified paraffin wax emulsion droplets are dispersed in an ethanol solution containing 1% to 2% ammonium perfluorooctanoate by mass, and then filtered, washed, and the paraffin wax is dissolved in chloroform, and then collected by centrifugation to obtain amphiphilic nanoparticles; The catalyst is nickel or an amphiphilic catalyst, and the amphiphilic catalyst is obtained by compounding NiMo and CoMo in a mass ratio of 1:(1-2).
2. The heavy oil chemical composite viscosity reducer according to claim 1, characterized in that: 35-45 parts of aromatic polyisobutylene succinic acid imide polymer, 15-18 parts of amphiphilic active agent, 8-12 parts of catalyst and 23-27 parts of organic base.
3. The heavy oil chemical composite viscosity reducer according to claim 1, characterized in that: The aromatic polyisobutylene succinic acid imide polymer is subjected to modification treatment, and the modification treatment process comprises the following steps: The aromatic polyisobutylene succinic acid imide and benzyl bromide are mixed, N, N-dimethylformamide is added to dissolve, and then sodium carbonate catalyst is added to reflux reaction at 60° C.-90° C., and then centrifuged and dried in sequence to obtain a benzyl-branched aromatic polyisobutylene succinic acid imide polymer; The molecular weight of the aromatic polyisobutylene succinic acid imide is greater than 500, and the molar number of the grafted benzyl group is 5-10.
4. The heavy oil chemical composite viscosity reducer according to claim 1, characterized in that: The amphiphilic catalyst is prepared by compounding NiMo and CoMo in a mass ratio of 1:
1.
5. A method for preparing a heavy oil chemical composite viscosity reducer according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: Aromatic polyisobutylene succinic acid imide polymer, amphiphilic active agent, catalyst, organic base and water are sequentially added into a reaction container and mixed at a temperature of 60-80° C. to obtain a heavy oil chemical composite viscosity reducer.
6. An oil recovery process, characterized in that: The oil recovery process uses a heavy oil chemical composite viscosity reducer as claimed in any one of claims 1 to 4, Among them, heavy oil refers to oil reservoirs with a burial depth of more than 1,800 meters, a permeability of less than 300mD, a crude oil viscosity greater than 10,000mPa·s, a calcium ion content greater than 3,000mg / L, and a magnesium ion content greater than 3,000mg / L.
Citation Information
Patent Citations
Preparation technology and usage method for high-conductivity heat transfer oil
CN104388056A
Viscosity reducer of petroleum crude oil
CN105950128A